2014
DOI: 10.1108/sampj-01-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of green strategy by Danish firms

Abstract: Purpose – The purpose of this study was to examine the issue of corporate environmentalism from a managerial perspective, specifically in connection to top management commitment and the need for competitive advantage, which can be integrated into the decision making of environmental strategies. Design/methodology/approach – This study uses data from a recent online survey of 77 Danish firms. Surveyed firms in the study were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
13
0
2
Order By: Relevance
“…Therefore, the greening of companies has to be conceived beyond the economic level of the company and is legal from a legal point of view and with important stakeholders (Moini et al, 2014). Also, Miles and Covin (2000) find that environmental motivation may come from the reputation associated with corporate greening, as it can ultimately improve a company's marketing and financial performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the greening of companies has to be conceived beyond the economic level of the company and is legal from a legal point of view and with important stakeholders (Moini et al, 2014). Also, Miles and Covin (2000) find that environmental motivation may come from the reputation associated with corporate greening, as it can ultimately improve a company's marketing and financial performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Research (Duarte & Cruz-Machado, 2013) recognize Green Up Lean & Green strategies. Not many found that using Moini, Soresen, and Kristiansen (2014) measurement modifications takes into account content analysis, which uses 4 themes, starting with formulating and pursuing a green strategy, the level of management involvement in the green strategy, changes in the business model of the company and the organization and Green Strategy Management to measure the extent to which a green industrial strategy can be formulated and pursued and what impact it has on the whole of the industry to understand the impact of climate change on the industry competence for emissions management, expressed in carbon emissions data disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, numerous environmental laws and regulations have been enacted, leading to an "ecorevolution" in economics (Lin, Chen, 2018). Green decision-making implies that decisions are made within environmental constraints, with an emphasis on conservation of natural resources and improvement in the quality of life of consumers (Sorensen et. al., 2014).…”
Section: Green Entrepreneurship As a Factor Of Innovationmentioning
confidence: 99%
“…The main idea is that a business can be profitable while having sustainable aims such as preserving the ecosystem, counteracting climate change, reducing environmental degradation and deforestation, improving farming practices and improving the environment, transporting drinking water, and/or maintaining biodiversity (Dean, McMullen, 2007). Therefore, environmental entrepreneurship could be an opportunity for reduction of environmental degradation "Greening the firm" is a pervasive topic as it touches on all aspects of a firm, including the firm's products and processes, business model, organizational design and management, and financial performance, making it a topic that is relevant across all sub-disciplines of business management (Sorensen et al, 2014).…”
Section: Green Entrepreneurship As a Factor Of Innovationmentioning
confidence: 99%
“…Research by Wahyuni and Ratnatunga (2015) investigated carbon strategies and carbon management adopted from companies that differed in level from Australia's national energy market. Danish Firm's adoption of green strategy (Hamid Moini, 2014) is a study that aims to examine the issue of corporate environmentalism from a managerial perspective, specifically related to top management commitment and competitive advantage, which are put together for decision making for environmental strategies.…”
Section: Introductionmentioning
confidence: 99%